Targeting Macrophage Mannose Receptor CD206 for Detection of Inflammation by Positron Emission Tomography - Andriana, Putri (fi=Turun yliopisto|en=University of Turku|, 2025)
Inflammation is a regulated adaptive response that protects the body’s normal function and homeostasis. However, when dysregulated, it can contribute to the development of chronic disease. Chronic cardiovascular diseases, such as atherosclerosis, can lead to myocardial infarction, in which the cardiomyocyte death is recognized as an inflammatory stimulus. Macrophages, professional phagocytes involved in the regulation of inflammation, can be polarized into M1 and M2 phenotypes depending on the mediators present in their microenvironment. The increase of M2 macrophages is a hallmark of the anti-inflammatory phase, as they play a significant role in resolving the inflammatory process, including cardiac healing after MI. The aim of this thesis was to develop and preclinically evaluate a novel positron emission tomography (PET) tracer for targeted M2 macrophage imaging. [18F]AlF-NOTA-D10CM, a fluorinated, mannosylated dextran derivative, was designed to recognize the mannose receptor CD206, which is predominantly expressed on M2 macrophages. To evaluate the suitability of [18F]AlF-NOTA-D10CM for PET imaging, studies were conducted on cells and experimental animals. In vitro cell studies revealed that [18F]AlF-NOTA-D10CM selectively binds to CD206-positive M2 macrophages, and the results were further confirmed in vivo using CD206 deficient versus wild-type mice. [18F]AlF-NOTA-D10CM PET enabled the detection of skin inflammation and lymph node activation in mice as well as inflammation associated with experimental acute MI in rats. Immunostaining of tissue samples verified that tracer uptake positively correlated with the amount of the macrophage mannose receptor CD206. In summary, these results demonstrate that [18F]AlF-NOTA-D10CM is a valid tool for PET imaging of CD206-positive M2 macrophages, and for non-invasive assessment of inflammation.